2008
DOI: 10.1021/ja800697g
|View full text |Cite
|
Sign up to set email alerts
|

Using α-Helical Coiled-Coils to Design Nanostructured Metalloporphyrin Arrays

Abstract: We have developed a computational design strategy based on the α-helical coiled-coil to generate modular peptide motifs capable of assembling into metalloporphyrin arrays of varying lengths. The current study highlights the extension of a two-metalloporphyrin array to a four-metalloporphyrin array through the incorporation of a coiled-coil repeat unit. Molecular dynamics simulations demonstrate that the initial design evolves rapidly to a stable structure with a small r.m.s.d. compared to the original model. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 12 publications
3
57
2
1
Order By: Relevance
“…For many of these goals, appropriately designed helical scaffolds hold much promise as they can provide structural stability and both topological and helical symmetry to facilitate multi-cluster molecules. In de novo porphyrin containing proteins, the helical topology has allowed the design of multi-cofactor nanowires [72, 73] – and similar strategies could be imagined for incorporating iron-sulfur clusters. As seen with existing helical designs, minimizing conformational strain by accommodating low-energy first shell ligand rotamers may be key for producing robust metalloproteins that are stable to redox cycling.…”
Section: Future Directionsmentioning
confidence: 99%
“…For many of these goals, appropriately designed helical scaffolds hold much promise as they can provide structural stability and both topological and helical symmetry to facilitate multi-cluster molecules. In de novo porphyrin containing proteins, the helical topology has allowed the design of multi-cofactor nanowires [72, 73] – and similar strategies could be imagined for incorporating iron-sulfur clusters. As seen with existing helical designs, minimizing conformational strain by accommodating low-energy first shell ligand rotamers may be key for producing robust metalloproteins that are stable to redox cycling.…”
Section: Future Directionsmentioning
confidence: 99%
“…A number of recent studies have reported the creation of symmetric, well-ordered assemblies composed of a few protein molecules (1)(2)(3)(4). Designing ordered assemblies of larger size and complexity has been a greater challenge.…”
mentioning
confidence: 99%
“…Water-soluble proteins have been designed to selectively bind nonbiological porphyrin-based cofactors (Bender et al, 2007; Cochran et al, 2005; Fry et al, 2010; McAllister et al, 2008), and one of these complexes has been redesigned to yield a redox-active membrane protein (Korendovych et al, 2010). This membrane protein (PRIME) was designed to form an antiparallel D 2 symmetric homo-tetramer.…”
Section: Computational Design Of Membrane Proteinsmentioning
confidence: 99%